Analisis Ketrampilan Bermain Tim Bolavoli Sidoarjo VS Surabaya pada Final Pekan Olahraga Provinsi (PORPROV) VIII Jawa Timur Tahun 2023 - Varendra Daffa Pratama; Soni Sulistyarto (Journal of Creative Student Research, 2025)
Sports play an important role in maintaining physical health. Sports not only help maintain fitness but also involve the automation of proper techniques in various sports disciplines. Volleyball is a team sport that requires coordination, teamwork, and technical skills to achieve success. The game involves two teams, each occupying half of the court, separated by a net. To achieve maximum performance, every player must master various basic techniques that serve as the foundation of the game. Mastering basic techniques such as serve, receive, attack, block, toss, and dig is key to success in volleyball. These skills not only support individual performance but also contribute significantly to the overall success of the team. This study aims to provide a comprehensive overview of team performance in the context of playing skills. By understanding the success and failure rates of volleyball teams from Sidoarjo and Surabaya during the Porprov VIII 2023, coaches and players can identify strengths and weaknesses, enabling more effective training and match strategies. The data collection method involved video analysis of the match results between Sidoarjo and Surabaya during Porprov VIII 2023 through YouTube. The results showed that the Sidoarjo team achieved a success rate of 76% in serving, 91% in receiving, 100% in tossing, 79% in attacking, 70% in blocking, and 86% in digging. Meanwhile, the Surabaya team achieved a success rate of 82% in serving, 67% in receiving, 95% in tossing, 60% in attacking, 48% in blocking, and 72% in digging. In conclusion, during the East Java Provincial Sports Week (PORPROV) 2023 match between Sidoarjo and Surabaya, the skill with the most frequent success for both teams was tossing. The key factor behind Sidoarjo's victory, based on these percentages, lies in their superiority in five playing skills: receiving, tossing, attacking, blocking, and digging. On the other hand, the factors behind the failure of the Surabaya team were blocking and receiving, as frequent errors in receiving hindered their ability to build effective attacks.